Interpretation of p16INK4a/Ki‐67 dual immunostaining for the triage of human papillomavirus‐positive women by experts and nonexperts in cervical cytology. Issue 4 (22nd December 2014) - Allia, Elena; Ronco, Guglielmo; Coccia, Anna; Luparia, Patrizia; Macrì, Luigia; Fiorito, Corinna; Maletta, Francesca; Deambrogio, Cristina; Tunesi, Sara; De Marco, Laura; Gillio‐Tos, Anna; Sapino, Anna; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The triage of human papillomavirus (HPV)‐positive women is needed to avoid overreferral to colposcopy. p16INK4a immunostaining is an efficient triage method. p16INK4a/Ki‐67 dual staining was introduced mainly to increase reproducibility and specificity compared with stand‐alone p16INK4a staining. METHODS Within a pilot project, HPV‐positive women were referred to colposcopy if cytology was abnormal or unsatisfactory or HPV testing was still positive after 1 year. For 500 consecutive women, a slide obtained during colposcopy was immunostained for p16INK4a/Ki‐67 and independently interpreted by 7 readers without previous experience with dual staining. Four of these readers were experts in cervical pathology and 3 were not. Kappa values for multiple raters, sensitivity, and specificity for cervical intraepithelial neoplasia type 2‐positive histology were computed. Because women with normal cytology were underrepresented, estimates for all HPV‐positive women were obtained as weighted means of cytology‐specific estimates. RESULTS The overall kappa for HPV‐positive women was 0.70 (95% confidence interval [95% CI], 0.60‐0.77). Kappa values were not found to be significantly different between expert and nonexpert readers with regard to cervical cytology but were significantly increased (P =. 0066) after consensus discussion. The overall specificity estimate for HPV‐positive women was 64.0% (95% CI, 57.4%‐70.2%): 66.7% (95% CI, 59.8%‐73.0%) for experts and 60.5% (95% CI, 59.8%‐73.0%) for nonexperts. Among women with abnormal cytology, the sensitivity was 85.5% (95% CI, 77.9%‐90.8%): 85.8% (95% CI, 77.9%‐91.2%) for experts and 85.1% (95% CI, 76.6%‐90.9%) for nonexperts. CONCLUSIONS p16INK4a/Ki‐67 immunostaining demonstrated good reproducibility and specificity when triaging HPV‐positive women. Dual‐staining interpretation can be performed, after short training, even by staff who are not experts in cervical cytology. This allows HPV‐based screening with triage to be performed in settings in which such expert staff is not available. Cancer (Cancer Cytopathol) 2015;123:212–218. © 2014 American Cancer Society.